Optimalisasi Self Healing bagi Santri Putri Pondok Pesantren Miftahul Mubtadiin Ar-Ridlo, al-Hamami dan Annur Krempyang Tanjunganom Nganjuk - Slamet Arofik; Hafidzul Umami (Janaka, Jurnal Pengabdian Masyarakat, 2021)
Social Mapping and social analysis conducted by Pokja 5 at the Mitahul Mubtadiin Ar-Ridlo, al-Hamami and Annur Kremp Islamic boarding schools showed that each cottage during the Covid-19 pandemic needed activities that had a "plus" value that was "therapist" . Therefore, we need activities that are not only positive and valuable but also entertainment that can be used as Self Healing, namely a (mental) healing process that is sufficient to involve oneself as a healer and generator of the suffering experienced. The method used in the service is Service Learning supported by the ABCD approach. The results of the service show that the service is able to bring the assisted partners, namely the female students of the Miftahul Mubtadiin Ar-Ridlo, al-Hamami and Annur Islamic boarding school towards a more "constrained" direction. The qualifications of the assisted partners are increasing and increasing. The ABCD approach philosophy is able to deliver assisted partners more quickly to achieve improvement. However, support from several parties is still needed to support further follow-up so that the program is able to produce optimal and permanent results.